Palliative paramedicine: Comparing clinical practice through guideline quality appraisal and qualitative content analysis. (September 2022) - Juhrmann, Madeleine L; Anderson, Natalie E; Boughey, Mark; McConnell, Duncan S; Bailey, Paul; Parker, Lachlan E; Noble, Andrew; Hultink, Amber H; Butow, Phyllis N; Clayton, Josephine M
Background: Palliative care is an emerging scope of practice for paramedicine. The COVID-19 pandemic has highlighted the opportunity for emergency settings to deliver palliative and end-of-life care to patients wishing to avoid intensive life-sustaining treatment. However, a gap remains in understanding the scope and limitations of current ambulance services' approach to palliative and end-of-life care. Aim: To examine the quality and content of existing Australian palliative paramedicine guidelines with a sample of guidelines from comparable Anglo-American ambulance services. Design: We appraised guideline quality using the AGREE II instrument and employed a collaborative qualitative approach to analyse the content of the guidelines. Data sources: Eight palliative care ambulance service clinical practice guidelines (five Australian; one New Zealand; one Canadian; one United Kingdom). Results: None of the guidelines were recommended by both appraisers for use based on the outcomes of all AGREE II evaluations. Scaled individual domain percentage scores varied across the guidelines: scope and purpose (8%–92%), stakeholder involvement (14%–53%), rigour of development (0%–20%), clarity of presentation (39%–92%), applicability (2%–38%) and editorial independence (0%–38%). Six themes were developed from the content analysis: (1) audience and approach; (2) communication is key; (3) assessing and managing symptoms; (4) looking beyond pharmaceuticals; (5) seeking support; and (6) care after death. Conclusions: It is important that ambulance services' palliative and end-of-life care guidelines are evidence-based and fit for purpose. Future research should explore the experiences and perspectives of key palliative paramedicine stakeholders. Future guidelines should consider emerging evidence and be methodologically guided by AGREE II criteria.